Circo Zanni e Linhas Aéreas: expressões da arte circense na cena contemporânea paulista - Mucci, Isabella [UNESP] (2013)
This study presents a research of the contemporary circus in Brazil by analyzing the trajectories of two circus companies working in São Paulo, Circo Zanni and Linhas Aéreas. Through theoretical study, historical survey and analysis of the works of these two companies, this research verifies the particularities of contemporary circus and its similarities and ruptures to traditional circus regarding the artistic field, their production, their mediators and their reception in order to provide material for future analysis and reflections concerning the art of the circus.